On horizontal biharmonic curves in the Heisenberg group Heis3 - Körpinar, Talat; Turhan, Essin (Springer Verlag, 2010)
In this paper, we study non-geodesic biharmonic curves in the Heisenberg group Heis3. We prove that there exist no non-geodesic horizontal biharmonic curves in the Heisenberg group Heis3.
Keywords: Biharmonic curve; Heisenberg group; Horizontal curve